The osservatori antimafia (mafia monitoring centre). Typologies and historical dynamics (Rivista di Studi e Ricerche sulla criminalità organizzata, 2015)
In recent years there have been an increase of osservatori antimafia (mafia monitoring centres), perceived as means whose associations, groups of citizens and municipal administrations develop with the purpose of monitoring the presence of organized crime in a given territory or social sector. The article presents a first census of the centres that arose in Italy between 1977 and 2015, investigating the evolutionary dynamics in relation to the history of the entire anti-mafia movement. In the study the author proposes its own classification of these realities, in order to understand their nature and composition and to observe their diffusion over time. The analysis also provides a mapping of the regions and provinces most affected by the presence of antimafia centres and those that are still lacking. The aim of the exploratory study is to fill a gap within the academic literature about the history of the anti-mafia movement, by studying one of its possible organizational forms and providing inputs for thinking about its potential weak and strong points.